1983
DOI: 10.1161/01.res.52.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of left ventricular mechanoreceptors with myelinated and nonmyelinated afferent vagal fibers in cats.

Abstract: SUMMARY. The purpose of this study was to determine the behavior of left ventricular mechanoreceptors with myelinated vagal afferents and to compare them with endings with nonmyelinated vagal afferents. Single unit activity was recorded from 13 endings with nonmyelinated vagal afferents (conduction velocity 2.1 ± 0.3 m/sec) and from 16 endings with myelinated vagal afferents (conduction velocity 7.3 ± 1.3 m/sec). Resting discharge frequencies of nonmyelinated afferents and of myelinated vagal afferents were 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 23 publications
(54 reference statements)
5
19
0
Order By: Relevance
“…18 Despite data suggesting that the activation of LV mechanoreceptors correlates linearly with LV end-diastolic pressure 19 and that enhanced contrac- tility may have a synergistic (but not independent) effect on receptor discharge, it has also been shown that acute hemorrhage (unloading of the left ventricle) triggers a paradoxical increase in mechanoreceptor activation. Therefore, one cannot disregard the possibility that the lower end-diastolic volume observed in the tilt-positive patients may have had a role in activating LV mechanoreceptors and triggering reflex bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…18 Despite data suggesting that the activation of LV mechanoreceptors correlates linearly with LV end-diastolic pressure 19 and that enhanced contrac- tility may have a synergistic (but not independent) effect on receptor discharge, it has also been shown that acute hemorrhage (unloading of the left ventricle) triggers a paradoxical increase in mechanoreceptor activation. Therefore, one cannot disregard the possibility that the lower end-diastolic volume observed in the tilt-positive patients may have had a role in activating LV mechanoreceptors and triggering reflex bradycardia and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures of stimulation and methods for controlling against simultaneous co-activation of other cardiorespiratory receptors are described below. Since cardiac mechanoreceptors are sensitive to changes in left ventricular enddiastolic pressure (LVEDP; Oberg & Thor en, 1972;Gupta & Thames, 1983), this variable only is quoted.…”
Section: Stimulation Of Cardiorespiratory Receptors and Controlling Fmentioning
confidence: 99%
“…Since pulse-modulated activity was only seen in cardiac vagal afferents during high and maintained levels of LVEDP (e.g. Oberg & Thor en, 1972;Gupta & Thames, 1983), this may explain the absence of pulse-modulated discharge in DS NTS neurones. In contrast, the lack of pulse modulation of NTS neurones receiving baroreceptor inputs probably reflects the small amplitude of the pulse pressure in the WHBP (see Methods and Results).…”
Section: Veratridine-driven Nts Neurones In the Mousementioning
confidence: 99%
“…The left ventricle is the site of many cardiac sensory receptors. [25][26][27] Nerve endings in the ventricle, the so called C-fiber of the vagus nerve, may be activated mechanically, either by cardiac stretching or by vigorous forceful contraction, or by other chemical stimuli such as catecholamines, veratridine and nicotine.28) The arterial baroreflex is an important buffer for elevations in arterial pressure. A similar reflex, which originates in the heart, is the cardiac mechanoreflex.29) Under normal circumstances, a reduction of systemic venous return reduces cardiac output and arterial blood pressure, which unloads the arterial baroreceptors and diminishes their inhibitory drive to the vasomotor center, resulting in reflex sympathetic activation.…”
mentioning
confidence: 99%